A case of extremely early cervical adenocarcinoma diagnosed only by endocervical curettage with macroscopic pelvic lymph node metastases - Jae Hak Jung; Byoung Ryun Kim (Korean Society of Obstetrics and Gynecology, 2019)
Microinvasive adenocarcinoma is not as well studied as microinvasive squamous cell carcinoma because diagnosis of adenocarcinoma cannot be ascertained for early invasive lesions. However, most clinicians consider a depth of invasion of 3 mm without lympho-vascular space invasion as the maximum limit for conservative management. Microinvasive cervical adenocarcinoma is characterized by a rare incidence of lymph node metastasis and very good prognosis. We describe a 62-year-old patient with an extremely early cervical adenocarcinoma which was detected only by endocervical curettage. However, she had multiple macroscopic pelvic node metastases. Clinicians should consider the probability of lymph node metastasis, although management of stage IA1 cervical adenocarcinoma may still be conservative.